Anthropological contributions to the study of climate: past, present, future. (15th April 2013) - Hastrup, Kirsten
Abstract: In the world of climate science there is an increasing demand for contributions from the social sciences, given that the current processes of climate change deeply affect societies. This article is a response to this call, with specific focus on past and potential contributions from anthropology, as we have known it from the 19th century onwards. It is shown how through the ages, different anthropological interests have shaped distinct perspectives on the entanglement of society and nature. It is argued that the present global concerns about climate change necessitate a refashioning of anthropology, and make it expedient to pay attention to the emergent global imaginaries. WIREs Clim Change 2013, 4:269–281. doi: 10.1002/wcc.219 This article is categorized under: Climate, History, Society, Culture > Disciplinary Perspectives